Synthesis, crystal structure and cholinesterase enzymes inhibitory activities of new pyridine alkaloid derivative - Ghalib, Gaza Murad; Hashim, Rokiah; Mehdi, Sayed Hasan; Da Silva, M. Fátima C. Guedes; Sulaiman, Othman; How, Fiona Ni Foong; Kawamura, Fumio; Jawad, Ali; Algamal, Yousif; Chan, Kit-Lam; Murugaiyah, Vikneswaran (India, 2015)
A new pyridine alkaloid derivative named as 2-(6-benzyl-4-oxo-5-phenyl-1,4-dihydro pyridine-3-yl)-benzoic acid ethylester (3) has been prepared by the reaction of ninhydrin with 1,3-diphenylacetonep-tosylhydrazone and the structure has been established with the help of spectral analysis and X-ray analysis. The title compound demonstrated potent inhibitory activity against butyrylcholinesterase (BChE; IC50 = 4.91 µM) comparable to physostigmine (IC50 = 4.72 x 10-1 µM). However it showed moderate inhibitory activity against acetylcholinesterase (AChE; IC50 = 82.00 µM)). It was BChE selective over AChE, in contrast to physostigmine, which was more AChE selective. Being a potent and selective BChE inhibitor, it may serve as a new class of drug for prevention of the progression of neurodegeneration as well for symptomatic treatment of Alzheimer patient.